Endogenous and Exogenous Stem/Progenitor Cells in the Lung and Their Role in the Pathogenesis and Treatment of Pediatric Lung Disease - Leibel, Sandra; Post, Martin (Frontiers in Pediatrics, 2016)
The lung is a complex organ with a vast surface area whose main function is to release cellular waste to be exhaled and to replenish the supply of oxygen to the tissues of the body. The conduction of air from the external environment is not without risks and the lung contains many specialized epithelial cell subtypes that protect the lung from foreign material and injury. Specialized cell subtypes are produced during lung development in the fetus, and injury to them due to genetic disease, premature birth or post-natal environmental injury may lead to devastating disease. Chronic diseases such as bronchopulmonary dysplasia, cystic fibrosis and pulmonary arterial hypertension contribute significantly to morbidity and mortality worldwide, yet successful interventions are often limited. Stem/progenitor cells have emerged as a potentially new preventative or therapeutic option. They are generally defined by the ability to undergo self-renewal and give rise to more differentiated cells. They are important in the early development of embryonic structures and organ differentiation in utero. Postnatally, they function in continued growth, maintenance and regeneration. Clinically, the immunomodulatory properties of some classes of stem/progenitor cells avoids the major obstacle of immunological rejection seen in organ transplantation and other cell therapies. This review highlights some known human progenitor/stem cells and the most recent clinical advances in stem cell therapies both in vivo and in vitro to prevent and treat pediatric lung disease.